The Influence Of Liquidity, Company Size, And Leverage On Financial Performance In The Coal Mining Manufacturing Sector Companies Listed On The Indonesian Stock Exchange (IDX) In 2020-2022 - Wahyu Wibowo; Muhammad Tahwin (Jurnal Manajemen Bisnis Eka Prasetya, 2024)
The purpose of this study is to prove the influence of liquidity, company size, and leverage on the financial performance of coal mining manufacturing sector companies listed on the Indonesian Stock Exchange (IDX) in 2020-2022. This research uses financial performance as the dependent variable and liquidity, company size, and leverage as independent variables. The population used in the study consists of all coal mining manufacturing sector companies consistently listed on the Indonesia Stock Exchange (IDX) during the period of 2020-2022, with a sample of 24 companies. The sampling method used in the study is purposive sampling. The data analysis technique used is multiple linear regression. The results of the study indicate that the liquidity variable has a non-significant positive effect on financial performance. Meanwhile, the company size and leverage variables have a non-significant negative effect on financial performance. From the determination test, the Adjusted R square value is obtained at 0.055 or 5.5%, which can be interpreted as liquidity, company size, and leverage in this regression model are able to explain 5.5% of the dependent variable financial performance within the model